A facile approach to fabricate a UV/heat dual-responsive triple shape memory polymer. Issue 1 (19th November 2014) - Wu, Y.; Hu, J.; Zhang, C.; Han, J.; Wang, Y.; Kumar, B.
Abstract : In the present work, a facile approach was employed to fabricate a UV/heat dual-responsive triple shape memory polymer (SMP) by simply mixing Zn(Mebip)2 (NTf2 )2, a metallosupramolecular unit formed by coordinating 2, 6-bis( N -methyl-benzimidazolyl)-pyridine (Mebip) ligands to zinc di[bis(trifluoromethylsulfonyl)-imide] (Zn(NTf2 )2 ), into one part of epoxy resin. Abstract : In the present work, a facile approach was employed to fabricate a UV/heat dual-responsive triple shape memory polymer (SMP) by simply mixing Zn(Mebip)2 (NTf2 )2, a metallosupramolecular unit formed by coordinating 2, 6-bis( N -methyl-benzimidazolyl)-pyridine (Mebip) ligands to zinc di[bis(trifluoromethylsulfonyl)-imide] (Zn(NTf2 )2 ), into one part of epoxy resin. Dissimilar to previously reported UV sensitive SMPs with sophisticated molecular structure and relatively poor mechanical properties, the advantage of this approach is that the UV-sensitivity was simply achieved by employing Zn(Mebip)2 (NTf2 )2, a UV-heat transfer compound, into the polymer matrix without significant sacrifice of thermal and mechanical properties. Also thanks to the light–heat transfer nature of Zn(Mebip)2 (NTf2 )2 and segmented material structure, the resulting polymer displayed UV sensitivity to the composite part, while leaving the shape of the neat SMP part unchanged under the UV source (solely thermal sensitive). Thus the resulting composite displayed an excellent UV and heat selective localized triple shape memory effect.